Macrobenthic communities in the polymetallic nodule field, Indian Ocean, based on multicore and box core analysis - Gaikwad, Santosh; Sautya, Sabyasachi; Damare, Samir; Mascarenhas-Pereira, Maria Brenda Luzia; Gawas, Vijayshree; Patil, Jayesh; Nanajkar, Mandar; Bukhari, Sadiq (Frontiers in Marine Science, 2024)
Managing deep-sea mining is challenging due to limited data on species and habitat distribution, hindering decision-making. In less-explored polymetallic nodule sites in the Indian Ocean, management approaches are deemed unfeasible due to a substantial lack of data. In this study, we aim to bridge the knowledge gap through a detailed analysis of the macrobenthos (fauna > 300 µm) obtained with two sampling gears (multi- and box corer) in potential impact, preservation, and reference zones in the Central Indian Ocean Basin. In total, 337 individuals were categorized into 106 morphospecies and 18 higher taxa. The lowest abundance was reported in the box corer. Nematodes and copepods dominated the macrobenthos community, whereas polychaetes and tanaidaceans were the more prevalent macrofaunal taxa. Carbohydrates and total organic carbon showed a notable positive correlation with polychaetes, isopods, and bivalves, indicating their influence on larger-sized taxa. Various functional traits, i.e., less motile, discretely motile, biodiffusors, and upward/downward conveyers, were dominant in the study area. The comparative analysis of multi- and box corer sampling reveals distinct patterns in macrobenthic diversity, emphasizing the importance of employing both gears for accurate functional analysis. The paper underscores the significance of including large meiofaunal taxa in macrofauna analyses for assessing deep-sea ecosystem functioning and services. Additionally, the findings contribute significantly to environmental baseline and impact assessment, a crucial aspect of sustainable management in a highly promising polymetallic nodule mining area, aligning with the goals of exploring.